2018
DOI: 10.1016/j.alit.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization to a whole egg by rush oral immunotherapy improves the quality of life of guardians: A multicenter, randomized, parallel-group, delayed-start design study

Abstract: rOIT induced desensitization to egg and thus improved the QOL of guardians; however, the participants experienced frequent allergic reactions due to the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 16 publications
0
68
0
1
Order By: Relevance
“…OIT studies have employed a 2-week elimination before OFC, 28,29 F I G U R E 3 Changes in casein-sIgG and sIgG 4 levels between the baseline and after 3 y. A, Casein-sIgG level in the LOIT group and the historical control group.…”
Section: Discussionmentioning
confidence: 99%
“…OIT studies have employed a 2-week elimination before OFC, 28,29 F I G U R E 3 Changes in casein-sIgG and sIgG 4 levels between the baseline and after 3 y. A, Casein-sIgG level in the LOIT group and the historical control group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients (43 patients, 37 males and 6 females, average age 7.3 ± 2.1 years) were confirmed to have hen's egg allergy by oral challenge test at the enrollment and received rush OIT that enabled 38 participants to eat about 1 egg (60 g) and 1 g of egg white powder per day without unbearable adverse effects, such as refractory gastroenteritis and/or severe anaphylaxis (28). These patients kept eating this amount of egg for 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…143 A Japanese study concluded that rush OIT to egg was able to induce desensitization, but caused frequent adverse events. 144 A Spanish study of 101 children with egg allergy randomized to faster (dose increase of 30% weekly plus 5% daily) or slower (30% weekly) concluded that the faster group was more likely to reach maintenance (96.15% vs 75.80%) and had fewer allergic reactions. 145 The target or maintenance dose of OIT varied greatly in studies and affects the goal outcome of OIT, that is, introduction into the diet vs protection from cross-contamination.…”
Section: Clinic Al Mark Er S and Pro Cedur Al Fac Tor S Of Tre Atmementioning
confidence: 99%